2005
DOI: 10.1051/0004-6361:20052916
|View full text |Cite
|
Sign up to set email alerts
|

Abundances in giant stars of the globular cluster NGC 6752

Abstract: Abstract. Recent theoretical yields and chemical evolution models demonstrate that intermediate-mass AGB stars cannot reproduce the observed abundance distributions of O, Na, Mg, and Al. As a further observational test of this finding, we present elemental abundance ratios [X/Fe] for 20 elements in 38 bright giants of the globular cluster NGC 6752 based on highresolution, high signal-to-noise spectra obtained with UVES on the VLT. This is the most complete spectroscopic analysis of this cluster in terms of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
213
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(256 citation statements)
references
References 129 publications
37
213
6
Order By: Relevance
“…It was not until the comprehensive study of Sneden et al (1991) that this trend was clearly defined in a robust way, resting on measurements in a large sample of stars. Recent studies of field (Mishenina et al 2002;Bihain et al 2004) and Globular Cluster stars (Shetrone et al 2001(Shetrone et al , 2003Simmerer et al 2003;Yong et al 2005) have confirmed this trend (see Fig. 1 of Bisterzo et al 2004).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…It was not until the comprehensive study of Sneden et al (1991) that this trend was clearly defined in a robust way, resting on measurements in a large sample of stars. Recent studies of field (Mishenina et al 2002;Bihain et al 2004) and Globular Cluster stars (Shetrone et al 2001(Shetrone et al , 2003Simmerer et al 2003;Yong et al 2005) have confirmed this trend (see Fig. 1 of Bisterzo et al 2004).…”
Section: Introductionmentioning
confidence: 69%
“…For NGC 6752 we can rely on the recent analysis by Yong et al (2005), who analysed 38 giants in this cluster, making use of high-resolution high-S/N ratio UVES spectra. The atomic data used by Yong et al (2005) are the same as those here used. The analysis is based on 1D ATLAS models and LTE spectrum synthesis.…”
Section: Observations and Equivalent Width Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average number of Fe i and Fe ii lines measured in a given star was 29 and 3, respectively. Following Yong et al (2005), we estimate that the internal uncertainties in T eff , log g and ξt are 30 K, 0.1 a The digits to the left of the decimal point are the atomic number. The digit to the right of the decimal point is the ionization state ("0" = neutral, "1" = singly ionised).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Smith et al (2005) noted that stars in M4 showed evidence for a Na-F anticorrelation (an F spread was also found in NGC 6712; Yong et al 2008a), while Pasquini et al (2005) and Bonifacio et al (2007) found a Na-Li anticorrelation in NGC 6752 and 47 Tucanae, respectively. The Mg-Al anticorrelation is of particular interest, because from data for NGC 6752 (Yong et al 2005), it is apparent that there is a larger spread in Al relative to Fe, on the order of ∼ 1 dex or more, but only a modest spread of ∼ 0.3 dex in Mg relative to Fe. A further important test for any model is determining how well it can reproduce the Mg isotopic ratios observed in GC stars (e.g., in NGC 6752; Yong et al 2003), which show a positive correlation between 26 Mg and Al, and an anticorrelation between the dominant 24 Mg and Al.…”
Section: Introductionmentioning
confidence: 99%